IT and the strategic growth agenda - Nunes, Paul F.; Michael, Gavin
A small but growing group of business leaders see IT as a way to spur change that prevents a company from peaking, then fading when its revenue growth stalls. They put IT to work to support strategy-to anticipate and respond to customers demands,renew their management teams and strengthen the layers of talen they'll need if they're to weather the bad times and grow fast when business is good.
Keywords: IT; S-curve.; Strategic Growth; Technologies; Finacial performance